Unknown primary large-cell neuroendocrine tumor - Sara Póvoa; Daniela Azevedo; Cristiana Marques; Helena Barroca; Andreia Costa (University of São Paulo, 2018)
Large-cell neuroendocrine tumors (NETs) are poorly differentiated malignancies of rare incidence and aggressive nature. NETs mostly arise in the lung followed by the gastrointestinal tract, although they are potentially ubiquitous throughout the body. Primary unknown NET has a worse prognosis and shorter survival comparing with other NETs, with limited available data in the literature concerning this subgroup. The authors report the case of large-cell NET with supraclavicular lymph node presentation. Total excisional biopsy revealed an enlarged adenopathy 18 × 15 × 10 mm, which was extensively infiltrated by a solid malignant neoplasm composed of large cells with granular chromatin, nuclear pseudo-inclusions, high mitotic index, and focal necrosis, with a Ki 67 index 25-30% and positive immunohistochemical study for the expression of cytokeratin 8/18, chromogranin, synaptophysin, and thyroid transcriptional factor-1 (TTF-1). There was no evidence of primary location apart from two infracentimetric lung lesions that could not be accessed for biopsy and were negative at both somatostatin receptor scintigraphy and positron emission tomography. The NET relapsed with three mediastinal masses, so the patient was started on chemotherapy with carboplatin and etoposide with initial total response. Early progression showed no response to further chemotherapy regimens (temozolomide, oral etoposide); therefore, the patient was treated with local radiotherapy. This patient has an atypical long survival (54 months) compared to the literature data. In fact, there are few long-term survivors of large-cell NET and they are all related to complete surgical resection.